Kepuasan kerja dan loyalitas karyawan: Menguji peranan Organizational Citizenship Behavior sebagai mediator: Job satisfaction and employee loyalty: Testing the role of Organizational Citizenship Behavior as a mediator - Desyantoro, Irwan; Sari, Dewi Puspita; Triamelia, Cristine Roselvia (Persona:Jurnal Psikologi Indonesia, 2024)
Retaining employee loyalty is a major challenge in the business world, particularly in the competitive property development industry, as faced by PT. XYZ. Employee loyalty significantly impacts productivity and the company's image. Job satisfaction and Organizational Citizenship Behavior (OCB) are crucial factors influencing employee loyalty, especially in addressing high turnover rates and variations in employee performance. This study aims to determine the direct and indirect effects of job satisfaction, Organizational Citizenship Behavior, and employee loyalty at PT XYZ. The research employs a quantitative method with a saturated sample approach involving 145 employees. Data were collected using structured questionnaires based on a job satisfaction scale (α= 0.855), an Organizational Citizenship Behavior scale (α= 0.834), and an employee loyalty scale (α= 0.897). Data analysis was conducted using mediation analysis through IBM SPSS v.25 (PROCESS Hayes-model 4). The findings indicate that job satisfaction, directly and indirectly, affects employee loyalty, with Organizational Citizenship Behavior serving as a significant mediation. These results highlight the importance of enhancing job satisfaction and fostering Organizational Citizenship Behavior as strategies to strengthen employee loyalty within organizations.